PENGETAHUAN TENTANG BAHAYA MEROKOK, PAPARAN IKLAN ROKOK DAN PENGARUH SOSIAL DENGAN STATUS MEROKOK PADA SISWA-SISWI SMU NEGERI DI KABUPATEN BREBES - , Nur Azizah Utami Dewi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Knowledge about dangers of smoking is very important to prevent a person from smoking behavior. Peer pressure, personal appearance, curiosity, stress, boring, being masculin and showed resistance, are things can be contributed adolescent began smoking. At side of peer factors, smoking behavior could be affected by family environment. Adolescent become smokers as affected by his own parents as a heavy smoker, which give chance to all children to imitate. Cigarette ads in the sidewalks or aired by the mass media also very influential an adolescent smoking behavior. Objective : This research was conducted to find the relationship between knowledge about the dangers of smoking, exposure to cigarette advertising, peer influence, family environment (parents) with decision to smoke on students in high school in Brebes Regency. Method : This kind of research was decriptive (quantitative), with cross sectional design. Population of this study were second grade students in high school. Minimum sample size was conducted with univariate analysis, bivariate analysis and mutivariate analysis was carried out to analyze the data. Result : There was significant relationship between level of knowing about the dangers of smoking and students decision to smoke. There was a significant relationship between exposure to cigarette advertisement and decision to smoke. There was a significant relationship between peer pressure and decision to smoke. There was a significant relationship between family environment and the decision to smoke. Conclusion : smoking behavior in adolescents, particulary high school students affected by knowledge of the dangers of smoking, exposure to cigarette advertising and social influence